Padrões de coexistência e utilização do hábitat por duas espécies de Herpsilochmus (Aves: Thamnophilidae) - França, Karol Lyncoln B. de O. de (2012)
How ecologically similar species are able to coexist has always generated great interest in the scientific community. Classical niche theory predicts that species coexistence is only possible when they segregate in at least one dimension of the ecological niche, thus leading to ecological differentiation among species. However, recent work has shown that species that are more similar in some ecological traits are the ones more prone to be able to coexist (environmental filter). The knowledge of how these forces act shaping ecological communities can reveal co-existence strategies, providing important information for management and conservation of the species. This study tested these hypotheses using a pair of coexisting species of Herpsilochmus, H. pectoralis and H. sellowi. In this study I use high resolution (50 x 50 m) ecological niche models to Identify which environmental factors best predict species occurrence. Next, I calculate the overlap in habitat use by species and build null models to test the hypothesis of spatial niche segregation. In addition, I obtain the selectivity parameters of habitat use to test whether the species H. pectoralis (larger body size) is less selective than H. sellowi (smaller body size) as stated in the literature for other species. The results reject the ecological equivalence among species, revealing that the species of Herpsilochmus explore the habitat differently, having different environmental niches. The hypothesis of environmental filter was not observed in my analysis, the observed overlap in habitat use among species was lower than expected by chance. Evidence that Herpsilochmus are spatially segregating reinforces the hypothesis of interspecific competition as the predominant force in the selection of microhabitat of the species. However, more data and experiments are necessary to state categorically that the observed pattern is a result of current or past competition